2015
DOI: 10.1007/s00402-015-2353-0
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation is a risk factor for poor outcome after supination external rotation type ankle fractures

Abstract: The results of this study suggest that concurrent dislocation at time of ankle fracture is associated with worse radiographic and functional outcomes, but not an increase in superficial or deep infection. The results from this study may be helpful in counseling patients regarding expected clinical outcomes after ankle fracture-dislocation and in the surgical management of this complex injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 17 publications
2
61
0
Order By: Relevance
“…41,47 Increased soft-tissue injury has been shown to result in an increased rate of postoperative complications when not properly addressed. 8,22,47 One review of surgical complications in 121 ankle fractures found that ankle fracture-dislocations (n ¼ 41; 34%) had 3 times as many major complications, including infection, compared with standard fractures (19% vs 6.3%, P < .05). 22 In that same report, fractures-dislocations, which were not expeditiously treated, were found to have a higher major soft-tissue complication rate compared with standard ankle fractures (44% vs 5.3%).…”
Section: Soft-tissue Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…41,47 Increased soft-tissue injury has been shown to result in an increased rate of postoperative complications when not properly addressed. 8,22,47 One review of surgical complications in 121 ankle fractures found that ankle fracture-dislocations (n ¼ 41; 34%) had 3 times as many major complications, including infection, compared with standard fractures (19% vs 6.3%, P < .05). 22 In that same report, fractures-dislocations, which were not expeditiously treated, were found to have a higher major soft-tissue complication rate compared with standard ankle fractures (44% vs 5.3%).…”
Section: Soft-tissue Injurymentioning
confidence: 99%
“…40 Some recent studies, however, have shown no significant association between postoperative infections and wound complications when comparing standard ankle fractures to ankle fracture-dislocations. 47,56 In these reports, there was a significant number of ankle fracture-dislocations that were treated initially with the application of temporary external fixators and delayed operative intervention (19% vs 49%, P ¼ .003). 47 The use of external fixation and delayed surgery has been shown to be effective in other fractures with considerable soft-tissue injury such as pilon fractures.…”
Section: Soft-tissue Injurymentioning
confidence: 99%
“…External fixators already play a fundamental role in the local damage control of ankle fracture dislocations not only to promote stabilization and comfort to the patient but also to improve soft tissue healing while waiting for definitive fixation [3,11,12,16,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Local conditions are of crucial importance for the correct surgical planning, in both emergency treatment and definitive treatment [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation